Pedagogical Implications of Simmel's Relativism. The Strasbourg Lectures on Pedagogy (1915-1916) - Amat, Matthieu (Simmel Studies, 2019)
Simmel's relativism aims to achieve the modern shift from substance to function without falling into pure sociological functionalism and generalized sceptical dissolution. This relativism would like to be at the same time a theory of objective forms of culture, a critique of modern forms of life and culture and a philosophical practice and attitude. That is why it is always both a philosophy of life and a philosophy of culture. Based on the pedagogy courses held by Simmel in Strasbourg in 1915/1916, this article outlines the consequences of this relativism in terms of pedagogy and philosophy of education. In particular, it considers ways to mitigate the "tragedy of culture", that is to promote the mobility and individuation of life without sacrificing the consistency of objective forms of culture.